Role of Hip Injury and Giving Way in Pain Exacerbation in Hip Osteoarthritis: An Internet‐Based Case–Crossover Study. Issue 6 (10th May 2019) - Fu, Kai; Makovey, Joanna; Metcalf, Ben; Bennell, Kim; Zhang, Yuqing; Asher, Rebecca; Robbins, Sarah; Deveza, Leticia; Hunter, David J.
Abstract : Objective: To evaluate the association between hip injury/giving way and hip pain exacerbations in patients with symptomatic hip osteoarthritis (OA). Methods: We conducted an internet‐based case–crossover study to assess hip injury and giving way for hip pain exacerbation. Eligible participants with symptomatic hip OA were followed up for 90 days and asked to complete online questionnaires at baseline and 10‐day intervals (control periods). They also logged on to the study web site to complete questionnaires for an episode of a hip pain exacerbation (case periods) defined as an increase of 2 points in pain intensity compared with the baseline rating on a numeric rating scale (range 0–10). The relationship of hip injury and giving way to the risk of pain exacerbation was examined using conditional logistic regression. Results: Of 252 patients recruited into the study, we included 133 patients (53%) who provided data from both case and control periods. Hip injury during the last 7 days increased the risk of hip pain exacerbation (odds ratio [OR] 2.74 [95% confidence interval (95% CI) 1.62–4.62]). The hip giving way during the last 2 days was associated with an increased risk of hip pain exacerbation (OR 2.10 [95% CI 1.30–3.39]) and showed a significant relationship between the number of hip giving way events and the risk of hip pain exacerbations ( P < 0.001). Conclusion: Hip injury and episodes of the hip giving way were significantly related to pain exacerbation in patients with symptomatic hip OA. Methods to prevent exposure to injury may help to reduce the burden of pain in patients with hip OA.